Mental health risk factors influencing metabolic syndrome among secondary school teachers of Mysore city, India - Narayanappa, Shashikala; Manjunath, Renuka; Kulkarni, Praveen (International Journal Of Community Medicine And Public Health, 2017)
Background: Metabolic syndrome has been suggested to be an intermediate pathway between depression and CVD wherein, chronic stress due to prolonged exposure to work stress, repeated stress over a period of time damages the HPA axis resulting in a maladaptive process as well as inflammatory factors like CRP which causes depression and poor health habits, leading to development of metabolic syndrome. The risk factors causing stress among the school teachers is very high as compared to other professional groups which not only affects their health but also adversely affects the students and their learning environment. The interventions have been mainly to reduce the level of work related stress and improve their performance in teaching, but have neglected a holistic approach to improve their overall health conditions. Methods:Cross sectional study was done in Mysore city among 320 Secondary school teachers aged 20 years and above, with at least one year of teaching experience. A self-administered, pretested and structured questionnaire based on the WHO steps approach for NCD, Gurmeet Singh’s Presumptive Stressful Life Events Scale (PSLES) for stress, PHQ 9 for depression and GHQ28 for general mental health status. Results: The prevalence of metabolic syndrome was 115 (38.3%). 30.6% had mild to moderate depression and only 2.3% had severe depression. 141 (47.0%) had moderate stress and only 42 (14%) had severe stress. The prevalence of minor psychiatric disorders (MPD) was 66 (22%). The mental health status did not have any statistically significant effect on the occurrence of MS or its risk factors. Conclusions:The poor mental health status was significantly associated with high fasting blood glucose levels, moderate to severe depression was significantly high among females and stress was associated with diastolic blood pressure, TGs and dyslipidemia.